Visual Basic . NET database programming - Stephens, Rod, 1961- (Que, 2002)
Visual Basic.NET Database Programming teaches with real-world scenarios how to load, display, manipulate, modify and save data in databases. It shows the reader how to build multi-tier applications that implement enterprise-wide business solutions, build Web Servers, manage large amounts of data, find specific records, sort data, perform complex queries, and use XML--an integral part of data handling in Visual Basic.NET.